Association Between Riboflavin Intake and Telomere Length: A Cross-Sectional Study From National Health and Nutrition Examination Survey 1999–2002 - Chen, Weihua; Shi, Shanshan; Jiang, Yizhou; Chen, Liling; Liao, Ying; Chen, Kaihong; Huang, Kun (Frontiers in Nutrition, 2022)
Background: Dietary habits and dietary intake affect telomere length, a reliable marker of biological aging and a predictor of chronic disease. Riboflavin (RF) is known as a water-soluble antioxidant vitamin, but its role in telomere length maintenance has yet to be elucidated. Objective: The purpose of this study was to examine the relationship between dietary RF intake and telomere length in a nationally representative sample of adults. Methods: Using the NHANES (1999-2002), telomere data of 4,298 participants aged ≥ 45 y were analyzed in a cross-sectional manner. Leukocyte telomere length was measured using the quantitative real-time polymerase chain reaction (qPCR). Dietary RF intake was assessed by a trained interviewer using 24-h dietary recall method. Generalized linear regressions were performed to evaluate the association between dietary RF intake and telomere length. Subgroup analyses were performed to further explore this relationship in sex and body mass index (BMI) subgroups. Results: Among the 3,788 participants included, the average telomere length was longer in females (P = 0.014), while they had a lower average RF intake compared to males (P < 0.001). There was a weak positive correlation between RF intake and telomere length both when unadjusted (β = 0.011; P = 0.037) and adjusted for age, sex, and ethnicity (β = 0.013; P = 0.033). Subgroup analyses showed a positive association between RF intake and the telomere length in female after adjusting for confounding factors (β = 0.029; P = 0.046). In the female subgroup, there were significant positive relationships between telomere length and RF intake in the obese group (β = 0.086, P = 0.022). Conclusions: Increased dietary RF intake was significantly associated with longer telomere length in middle-aged and older American females, especially in low RF intake obese female.